Observe to Instruct, Manage to Know: the Teaching of Materia Medica and Pharmacy in the Reform of the University of Coimbra (1772): (Revista Angelus Novus, 2023)
This article addresses the modernization process of teaching Materia Medica and Pharmaceutical Art at the University of Coimbra from its statutory reformulation of 1772. Starting from an investigation that prioritizes the epistemological transformations of medicine in the 18th century, the study aims to analyze the consolidation of an empirical-rational pedagogy in the context of the university reform conducted by the Marques de Pombal in the Portuguese Kingdom. We present the dynamics of medical education from the lessons of Dr. José Francisco Leal, professor responsible for teaching Pharmacy and Materia Medica at the university, examining the character of their teaching methodologies. Therefore, the text articulates an analysis between the 1772 Statutes and the Instituições de Farmácia, teaching material produced by Professor Leal. The results show that the reforms of the Faculty of Medicine sought to prioritize in its statutes, the assumptions of experimentalism and rational criticism of old medical doctrines, based on an Illustrated model of education that provided new training instruments for medical students.